2016
DOI: 10.1007/s11695-016-2387-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for the rs696217 SNP in the Preproghrelin Gene Predicts Weight Loss After Bariatric Surgery in Severely Obese Individuals

Abstract: Carrying a G to T substitution in rs696217 (preproghrelin gene) seems to mark a successful weight loss outcome; we also report for the first time that the rs1126535 C allele (CD40L gene) may predict a worse response to bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Table 4 summarizes studies identifying characteristics associated with weight loss response to MBS. A majority of these studies involve Roux-en-Y gastric bypass (RYGB), [100][101][102][103][104][105][106][107][108][109][110][111][112][113] with a few evaluating vertical sleeve gastrectomy (VSG), 114 laparoscopic adjustable gastric banding (LAGB), [115][116][117] biliopancreatic diversion (BPD), 118 sleeve gastroplasty, 119 or a pooling of data from multiple procedures. [120][121][122][123][124] Overall, studies exploring predictors of weight loss response to MBS in adolescents are rare.…”
Section: Metabolic and Bariatric Surgerymentioning
confidence: 99%
“…Table 4 summarizes studies identifying characteristics associated with weight loss response to MBS. A majority of these studies involve Roux-en-Y gastric bypass (RYGB), [100][101][102][103][104][105][106][107][108][109][110][111][112][113] with a few evaluating vertical sleeve gastrectomy (VSG), 114 laparoscopic adjustable gastric banding (LAGB), [115][116][117] biliopancreatic diversion (BPD), 118 sleeve gastroplasty, 119 or a pooling of data from multiple procedures. [120][121][122][123][124] Overall, studies exploring predictors of weight loss response to MBS in adolescents are rare.…”
Section: Metabolic and Bariatric Surgerymentioning
confidence: 99%
“…Ghrelin is expressed by GHRL gene, several SNP are informed for it. In literature is actively studied the SNP allele polymorphism with obesity [10,11], food behavior disorders [12] and metabolism disturbances [13], and also with gastric acid secretion [14] and fast stomach emptying [15,16]. Mutations in this gene can cause low levels of ghrelin, registered at obesity [17].…”
Section: Introductionmentioning
confidence: 99%
“…When Seip et al (2016) [ 26 ] evaluated 330 SNPs of genes involved in metabolic regulation they identified many genes that could be potential markers to discriminate changes in body mass index (BMI) one year after surgical intervention (LAGB or RYGB). Other authors suggested that polymorphisms, like the SNP of the preproghrelin gene (rs696217), could mark a successful weight loss outcome [ 27 ]. Table 1 lists recent studies that associate SNPs and bariatric surgery outcomes.…”
Section: Genetic Background and Bariatric Surgery Managementmentioning
confidence: 99%